(untitled) (Revista Contexto & Saúde, 2023)
Antihypertensive drugs are among the most prescribed drugs in basic health units. In this context, the objective of this study was to analyze the prescriptions for antihypertensive drugs in a basic health unit in the Western Health Region of the Federal District. This is an observational, descriptive, cross-sectional study, collecting secondary data. An analysis of 1,500 prescriptions was carried out, in which only 870 were considered valid. The most prescribed drugs were losartan, indapamide, hydrochlorothiazide, amlodipine and atenolol. Doctors were the most prevalent prescribers, followed by nurses. Rates higher than 90% were found in the prescriptions for the adoption of the Brazilian Common Denomination (DCB) and the List of Essential Medicines of the Federal District (REME-DF). The study contributes to the survey of elementary information for the qualification of services in the studied health region.